To determine the role of ultrasonography as a primary imaging modality as compared to MRI in patients with shoulder pain - Hardev V Barad; Viral Patel; Shreya Patel; Mamta Patel (Journal of Family Medicine and Primary Care, 2022)
Context: Prevalence of shoulder pain in general population worldwide ranges from 16 -26%. It is necessary to evaluate different causative factors in shoulder pain and explore the utility of ultrasonography in rotator cuff and non-rotator cuff diseases as a primary imaging modality and reserve MRI for unequivocal cases. Aims: To evaluate patients with shoulder pain using ultrasound as first line of imaging modality compared to MRI. Methods and Material: A Prospective Cross-sectional Descriptive and Analytical study was done in patients with shoulder pain referred to radiology department for USG and MRI. Statistical Analysis Used: Analysis was performed using STATA (14.2). Descriptive statistics was used to portray baseline profile of study population. Sensitivity, specificity, PPV, NPV and Kappa value used. Results: In the resent study the maximum patients were between 40-59 years with Male: Female ratio of 3.5:1. Trauma was the most common etiological factor and restricted range of motion was seen in 47 (94%). Supraspinatus tendon was the most common tendon to show abnormality followed by Subscapularis. For Supraspinatus tendon and Subscapularis tendon partial thickness tear- USG had a sensitivity of 90.62% and 100%, specificity of 88.88% and 95.74%, PPV of 93.5% and 60.00% and NPV of 84.21% and 100% respectively. Conclusion: Ultrasound although being operator dependent and not as accurate as MRI, provides rapid real time non-invasive cross-sectional imaging of joint and thus can be considered as primary modality for imaging rotator cuff pathologies, as it is readily available and cost effective.